2011
DOI: 10.1002/chem.201002614
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Generation of Diastereomers by Double Diboration of a Dialkyne

Abstract: During the last two decades, boron compounds have become established as versatile reagents in organic synthesis, and different methods have been developed for their preparation. Along with hydroboration, [1][2][3][4] transition-metalcatalyzed diboration [5] has become useful for the functionalization of unsaturated organic compounds. [6,7] This reaction is widely applicable to substrates such as alkynes [8,9] arynes, [10] alkenes, [11][12][13] carbenoids, [14,15] as well as diazo [16] and carbonyl compounds. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 44 publications
5
16
0
Order By: Relevance
“…The B–B bond in [2]-borametalloarenophanes has been cleaved by addition to alkynes using palladium and platinum catalysts, inserting the carbon–carbon triple bond into the B–B bridge. Braunschweig and co-workers were also able to isolate heterobimetallic compounds resulting from oxidative addition of the B–B bond to a platinum(0) compound (Scheme , right). ,,, Reaction with B 2 pin 2 or B 2 cat 2 resulted in boryl exchange and loss of the B–B bridge (Scheme , left) . Additionally, these complexes were found to be active catalysts in ethylene polymerization and ethylene/1-hexene copolymerization. , …”
Section: Synthesis Structure and Bonding Of Diboron(4) Compoundsmentioning
confidence: 99%
“…The B–B bond in [2]-borametalloarenophanes has been cleaved by addition to alkynes using palladium and platinum catalysts, inserting the carbon–carbon triple bond into the B–B bridge. Braunschweig and co-workers were also able to isolate heterobimetallic compounds resulting from oxidative addition of the B–B bond to a platinum(0) compound (Scheme , right). ,,, Reaction with B 2 pin 2 or B 2 cat 2 resulted in boryl exchange and loss of the B–B bridge (Scheme , left) . Additionally, these complexes were found to be active catalysts in ethylene polymerization and ethylene/1-hexene copolymerization. , …”
Section: Synthesis Structure and Bonding Of Diboron(4) Compoundsmentioning
confidence: 99%
“…Recently, the diboration chemistry of [ n ]boraferrocenophanes 33 and 48 has been successfully expanded to a variety of differently substituted dialkynes with varying electronic and steric properties 42,43. Dialkynes studied are depicted in Scheme and include common derivatives RCC–CCR ( 59 : R = Me; 60 R = Ph) and spacer‐bridged species (SiMe 3 )CC–X–CC(SiMe 3 ) ( 61 : X = E ‐C 2 H 2 ; 62 : X = 1,4‐C 6 H 4 ).…”
Section: Reactivity Of [2]borametalloarenophanesmentioning
confidence: 99%
“…(ii) Single diboration reactions with additional coordination of the pendant alkyne C–C triple bond to a [Pt(PEt 3 ) 2 ] complex fragment resulted in the formation of dinuclear complexes [(3,4‐η 2 ‐Fe{η 5 ‐C 5 H 4 –B(NMe 2 )} 2 –{R}C=C–CCR)Pt(PEt 3 ) 2 ] ( 67 and 68 ), if [3]diboraplatinaferrocenophane 48 was treated with spacer‐free dialkynes 59 and 60 under stoichiometric reaction conditions 43. (iii) Double diboration was eventually achieved for the sterically less congested dialkynes 61 and 62 applying both stoichiometric and homogeneous catalysis conditions 42,43. Reactions were conducted employing 2 equivalents of either 33 or 48 and enabled the isolation of dinuclear bis[4]diboradicarbaferrocenophanes of the type [1,4‐(Fe{η 5 ‐C 5 H 4 –B(NMe 2 )} 2 –{Me 3 Si}C=C) 2 X] ( 69 and 70 ).…”
Section: Reactivity Of [2]borametalloarenophanesmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Reactivity studies on these metalloarenophanes revealed their potential for further transformations, such as ringopeningp olymerization [7,[10][11][12] to produce metallopolymers or the functionalization of unsaturated organic substrates. [19][20][21][22][23][24][25][26][27][28] Herein, we focus on the manganese-containing complex [Mn(h 5 -C 5 H 5 )(h 6 -C 6 H 6 )],w hichi si soelectronic to ferrocene. Alongside [Cr(h 5 -C 5 H 5 )(h 6 -C 6 H 6 )] it represents ar are example of as ystem with ab enzene and ac yclopentadienyl ligand that has successfullyb een employed for the preparation of ansacomplexes.…”
Section: Introductionmentioning
confidence: 99%